A kind of water-based transfer coating with bending resistance and its application in transfer card

By adding modified polyurethane resin and modified aqueous styrene resin to the aqueous transfer coating, the shortcomings of the holographic brightness and bending resistance of the aqueous transfer coating are solved, and the high-brightness holographic effect and bending resistance are achieved, which meets the high-performance needs of the packaging industry.

CN119083232BActive Publication Date: 2025-04-15HUIZHOU HUIXIN IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411210211.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-04-15
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Existing water-based transfer coatings are generally worse than solvent-based transfer coatings in holographic brightness, and their bending resistance is not ideal, making it difficult to meet the improvement of anti-counterfeiting technology and appearance requirements in the packaging industry.

Method used

By adding modified polyurethane resin and modified aqueous styrene resin to the aqueous transfer coating, the components and preparation methods of the resin are optimized to improve the bending resistance and holographic brightness of the coating.

Benefits of technology

It has achieved the high-gloss holographic effect, excellent peeling properties and improved bending resistance of water-based transfer coatings, meeting the packaging industry's demand for high-performance transfer cards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020128550000111
    Figure BDA0005020128550000111
Patent Text Reader

Abstract

The present invention provides a folding-resistant water-based transfer coating and an application thereof in a transfer card. The folding-resistant water-based transfer coating comprises the following components by mass fraction: 10-15 parts of a modified polyurethane resin; 5-10 parts of a modified water-based styrene-acrylic resin; 10-15 parts of ethanol; 55-60 parts of deionized water; 0.1-0.2 parts of a dispersing aid; 0.07-0.12 parts of a leveling agent; and 0.1-0.13 parts of a defoaming agent. The water-based transfer coating of the present invention has a high-brightness holographic effect and excellent peelability, can improve the folding resistance of a transfer card, and has broad market value and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a water-based transfer coating with bending resistance and application thereof in a transfer card. Background Art

[0002] Transfer cardboard is a commonly used paper in the packaging industry. It is beautiful and elegant because it absorbs the advantages of traditional gold and silver cardboard, aluminum foil cardboard, and laser cardboard. It has the same glossiness despite having no plastic on its surface. At the same time, the aluminum layer in the transfer cardboard is quite thin compared to the aluminum foil cardboard, which can save aluminum materials. Its glossiness is higher than that of the aluminum foil cardboard, so it is increasingly favored by the market. Transfer cardboard has a wide range of applications and is often used in the packaging of food, tobacco, etc. It requires to be non-toxic, stable, environmentally friendly, and safe.

[0003] But at the same time, with the expansion of the field of use and the increasing application requirements, new requirements have been put forward for transfer cardboard. The water-based transfer coating is applied to polyester or other film products, dried and formed into a film, and then vacuum-plated with aluminum. Then the aluminum-plated film and paper are compounded together with a composite glue, and finally the film is peeled off to obtain vacuum aluminum-plated transfer paper. In order to meet the continuous improvement of anti-counterfeiting technology and appearance requirements, laser holographic transfer paper is widely used in the packaging field. At present, most laser holographic transfer papers are produced and prepared with solvent-based laser transfer coatings. Water-based laser holographic transfer paper is generally inferior to solvent-based laser holographic paper in holographic brightness, which greatly affects the product qualification rate and product appearance. Patent 201811122098.2 discloses a high-brightness holographic water-based transfer coating and its preparation method, which effectively solves the defect that water-based transfer coatings are generally inferior to solvent-based transfer coatings in holographic brightness, but the transfer cardboard prepared with it has poor bending resistance.

[0004] Therefore, there is an urgent need for a water-based transfer coating with bending resistance and its application in transfer cards. Summary of the invention

[0005] The purpose of the invention is to provide a water-based transfer coating with bending resistance and application of the coating in a transfer card.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A bending-resistant water-based transfer coating comprises the following components in mass fractions: 10-15 parts of modified polyurethane resin; 5-10 parts of modified water-based styrene-acrylic resin; 10-15 parts of ethanol; 55-60 parts of deionized water; 0.1-0.2 parts of dispersing aid; 0.07-0.12 parts of leveling agent; 0.1-0.13 parts of defoaming agent;

[0008] The preparation method of modified polyurethane resin is:

[0009] (1) mixing 25-30 parts by weight of polyol, 25 parts by weight of polyisocyanate, 3.5-4.0 parts by weight of dimethylaminopropyl acrylamide, 1.6-1.9 parts by weight of 1,4-butanediol, 0.4-0.7 parts by weight of trimethylolpropane, and 0.5-0.7 parts by weight of polyethylene glycol monomethyl ether, and reacting at 80-85° C. until NCO reaches a theoretical value of 2.5-2.8 wt %, to obtain a terminal isocyanate prepolymer; cooling to 60-65° C., and then adding 52-57 parts by weight of acrylic acid monomer and 2-2.4 parts by weight of triethylamine to obtain a polyurethane prepolymer;

[0010] (2) under stirring at 40-45° C., the polyurethane prepolymer containing acrylic acid monomers in step (1) is added dropwise to 110 parts by weight of water for 10-15 minutes, and 1.5-1.7 parts by weight of ethylenediamine is added to obtain a polyurethane emulsion;

[0011] (3) 30-35 parts by weight of water and 10-15 wt% of polyurethane emulsion are mixed, and the remaining polyurethane emulsion and 0.06-0.09 parts by weight of ammonium persulfate are added dropwise at 80-85° C. with stirring for 2-3 h. After the addition is completed, the temperature is kept warm for 30-40 min, cooled to 55-60° C., 0.04-0.06 parts by weight of tert-butyl hydroperoxide and 0.02-0.03 parts by weight of isoascorbic acid are added dropwise for 15-30 min, and the temperature is cooled to room temperature to obtain a modified polyurethane resin.

[0012] Furthermore, the polyol is a mixture of polycarbonate diol, polycaprolactone diol and polypropylene glycol in a mass ratio of 1:(1.3-1.6):(0.2-0.5).

[0013] Furthermore, the weight average molecular weights of the polycarbonate diol, the polycaprolactone diol and the polypropylene glycol are all 2000-3000.

[0014] Furthermore, the polyisocyanate is one or a combination of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and cyclohexane dimethylene diisocyanate.

[0015] Furthermore, the weight average molecular weight of polyethylene glycol monomethyl ether is 1400-1700.

[0016] Furthermore, the acrylic monomer is a mixture of butyl methacrylate, methyl methacrylate and hydroxyethyl acrylate in a mass ratio of (0.4-0.7):1:(1.5-1.8).

[0017] In the prior art, transfer cards usually use water-based polyurethane resin as the main component of the coating, but the bending resistance of the coating is not ideal. The present invention can improve the bending resistance of the water-based transfer coating by adding modified polyurethane resin to the water-based transfer coating. The present invention uses polyols and acrylic monomers in a specific ratio as reactants to combine hard and soft segments, which helps to improve the flexibility of the final product. At the same time, under this condition, the temperature resistance of the water-based transfer coating can also be improved. However, the holographic brightness of the water-based transfer coating is not ideal at this time.

[0018] Furthermore, the preparation method of the modified water-based styrene acrylic resin is as follows: by weight:

[0019] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.12-0.15 parts by mass of graphene oxide were mixed, ultrasonicated for 20-30 minutes, 50-55 parts by mass of N,N-dimethylformamide were added, stirred at 100-110° C. for 2-3 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;

[0020] (2) mixing 10 parts by mass of modified graphene oxide and 60-64 parts by mass of ethanol, then adding an aqueous solution of nano-titanium oxide, stirring at 55-60° C. for 2-3 hours, centrifuging, and freeze-drying to obtain modified graphene oxide;

[0021] (3) 30-35 parts of methyl methacrylate, 12-17 parts of hydroxyethyl acrylate, 6-12 parts of styrene, 40-45 parts of organosiloxane, 3-6 parts of emulsifier, 0.2-0.4 parts of ammonium persulfate, 1-1.3 parts of 1,4-butyrolactone, 0.35-0.38 parts of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5-7 parts of modified graphene oxide, and 200-220 parts of deionized water are mixed, and the mixture is heated to 80-85° C. for polymerization reaction for 3-4 hours under stirring, and then cooled to 30-40° C., and then ammonia water is added to adjust the pH value of the system to 7-7.5, and stirring is stopped and the mixture is cooled to room temperature to obtain a modified water-based styrene acrylic resin.

[0022] Furthermore, the organosiloxane monomer is a mixture of vinyltrimethoxysilane, vinyltriethoxysilane and allyltrimethoxysilane in a mass ratio of 1:(1.3-1.5):(0.2-0.5).

[0023] Furthermore, the emulsifier is octylphenol polyoxyethylene ether, and the octylphenol polyoxyethylene ether is OP-4.

[0024] Furthermore, the mass ratio of the modified graphene oxide to TiO2 is 10:1-3.

[0025] Furthermore, the graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and is purchased from Xianfeng Nano.

[0026] Furthermore, the average particle size of nano titanium oxide is 15nm, and the specific surface area is 30-100m 2 / g. Beijing Dekedaojin Technology Co., Ltd.

[0027] The present invention can improve the holographic brightness of water-based transfer coatings by adding modified water-based styrene-acrylic resin into the system. Nano-titanium oxide grafted onto the surface of graphene oxide as a hydrophobic group helps to improve its dispersibility in the resin system. Graphene oxide and nano-titanium oxide have a high specific surface area and a unique two-dimensional structure, and can serve as efficient light scattering centers, helping to improve the optical properties of the coating. The modified water-based styrene-acrylic resin can optimize the light propagation path inside the coating, reduce internal reflections, and thus improve the holographic brightness.

[0028] Furthermore, the dispersing aid is DI SPERBYK-192.

[0029] Furthermore, the leveling agent is German BYK-358N leveling agent.

[0030] Furthermore, the defoaming agent is TEGO 904W defoaming agent.

[0031] Furthermore, the preparation method of the bending-resistant water-based transfer coating is as follows: weigh the components, blend them, stir them evenly, and filter them through a 200-300 mesh filter to obtain the coating.

[0032] Application of a bending-resistant water-based transfer coating in a transfer card.

[0033] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0034] 1. The water-based transfer coating of the present invention has a high-brightness holographic effect and excellent peelability, can improve the folding resistance of the transfer card, and has broad market value and application prospects.

[0035] 2. The present invention can improve the bending resistance of the water-based transfer coating by adding modified polyurethane resin to the water-based transfer coating; at the same time, under this condition, the temperature resistance of the water-based transfer coating can also be improved.

[0036] 3. The present invention can improve the holographic brightness of the water-based transfer coating by adding modified water-based styrene acrylic resin into the system. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] This embodiment provides a water-based transfer coating with bending resistance, comprising the following components by mass fraction: 14 parts of modified polyurethane resin; 8 parts of modified water-based styrene-acrylic resin; 12 parts of ethanol; 57 parts of deionized water; 0.15 parts of dispersing aid; 0.09 parts of leveling agent; 0.12 parts of defoaming agent;

[0040] The preparation method of modified polyurethane resin is:

[0041] (1) 27 parts by weight of polyol, 25 parts by weight of polyisocyanate, 3.7 parts by weight of dimethylaminopropyl acrylamide, 1.8 parts by weight of 1,4-butanediol, 0.6 parts by weight of trimethylolpropane, and 0.6 parts by weight of polyethylene glycol monomethyl ether were mixed and reacted at 82° C. until NCO reached a theoretical value of 2.6 wt % to obtain a terminal isocyanate prepolymer; the mixture was cooled to 62° C., and then 55 parts by weight of acrylic acid monomer and 2.2 parts by weight of triethylamine were added to obtain a polyurethane prepolymer;

[0042] (2) under stirring at 42° C., the polyurethane prepolymer containing acrylic acid monomers in step (1) was added dropwise to 110 parts by weight of water for 12 minutes, and 1.6 parts by weight of ethylenediamine was added to obtain a polyurethane emulsion;

[0043] (3) 32 parts by weight of water and 12 wt% of a polyurethane emulsion were mixed, and the remaining polyurethane emulsion and 0.07 parts by weight of ammonium persulfate were added dropwise at 82° C. with stirring for 2.5 h. After the addition was completed, the mixture was kept warm for 35 min, cooled to 58° C., 0.05 parts by weight of tert-butyl hydroperoxide and 0.02 parts by weight of isoascorbic acid were added dropwise for 20 min, and the mixture was cooled to room temperature to obtain a modified polyurethane resin.

[0044] The polyol is a mixture of polycarbonate diol, polycaprolactone diol and polypropylene glycol in a mass ratio of 1:1.5:0.4.

[0045] The weight average molecular weight of the polycarbonate diol, the polycaprolactone diol, and the polypropylene glycol is 2,400.

[0046] The polyisocyanate is toluene diisocyanate.

[0047] The weight average molecular weight of polyethylene glycol monomethyl ether is 1500.

[0048] The acrylic monomer is a mixture of butyl methacrylate, methyl methacrylate and hydroxyethyl acrylate in a mass ratio of 0.6:1:1.7.

[0049] The preparation method of the modified water-based styrene acrylic resin is as follows: by weight:

[0050] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.14 parts by mass of graphene oxide were mixed, ultrasonicated for 25 minutes, 52 parts by mass of N,N-dimethylformamide were added, stirred at 105° C. for 2.5 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;

[0051] (2) 10 parts by mass of modified graphene oxide and 62 parts by mass of ethanol were mixed, and then an aqueous solution of nano-titanium oxide was added, stirred at 58° C. for 2.5 h, centrifuged, and freeze-dried to obtain modified graphene oxide;

[0052] (3) 32 parts of methyl methacrylate, 15 parts of hydroxyethyl acrylate, 10 parts of styrene, 42 parts of organosiloxane, 5 parts of emulsifier, 0.3 parts of ammonium persulfate, 1.2 parts of 1,4-butyrolactone, 0.37 parts of 1,4,7-trimethyl-1,4,7-triazacyclononane, 6 parts of modified graphene oxide, and 210 parts of deionized water were mixed, and the mixture was heated to 82° C. for polymerization reaction for 3.5 hours under stirring, and then cooled to 35° C., and then ammonia water was added to adjust the pH of the system to 7.2, and stirring was stopped and the mixture was cooled to room temperature to obtain a modified water-based styrene acrylic resin.

[0053] The organic siloxane monomer is a mixture of vinyl trimethoxy silane, vinyl triethoxy silane and allyl trimethoxy silane in a mass ratio of 1:1.4:0.3.

[0054] The emulsifier is octylphenol polyoxyethylene ether, and the octylphenol polyoxyethylene ether is OP-4.

[0055] The mass ratio of modified graphene oxide and TiO2 is 10:3.

[0056] The graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and was purchased from Xianfeng Nano.

[0057] The average particle size of nano titanium oxide is 15nm, and the specific surface area is 30-100m 2 / g. Beijing Dekedaojin Technology Co., Ltd.

[0058] The dispersing aid is DI SPERBYK-192.

[0059] The leveling agent is BYK-358N leveling agent from Germany.

[0060] The defoaming agent is TEGO904W defoaming agent.

[0061] The preparation method of the bending-resistant water-based transfer coating is as follows: weigh the components, blend them, stir them evenly, and filter them through a 200-mesh filter to obtain the coating.

[0062] Example 2

[0063] This embodiment provides a water-based transfer coating with bending resistance, comprising the following components by mass fraction: 10 parts of modified polyurethane resin; 10 parts of modified water-based styrene acrylic resin; 15 parts of ethanol; 55 parts of deionized water; 0.2 parts of dispersing aid; 0.07 parts of leveling agent; 0.13 parts of defoaming agent;

[0064] The preparation method of modified polyurethane resin is:

[0065] (1) 25 parts by weight of polyol, 25 parts by weight of polyisocyanate, 4.0 parts by weight of dimethylaminopropyl acrylamide, 1.6 parts by weight of 1,4-butanediol, 0.7 parts by weight of trimethylolpropane, and 0.5 parts by weight of polyethylene glycol monomethyl ether are mixed and reacted at 85° C. until NCO reaches a theoretical value of 2.5 wt %, thereby obtaining a terminal isocyanate prepolymer; the mixture is cooled to 65° C., and then 52 parts by weight of acrylic acid monomer and 2.4 parts by weight of triethylamine are added to obtain a polyurethane prepolymer;

[0066] (2) under stirring at 40° C., the polyurethane prepolymer containing acrylic acid monomers in step (1) was added dropwise to 110 parts by weight of water for 15 minutes, and 1.5 parts by weight of ethylenediamine was added to obtain a polyurethane emulsion;

[0067] (3) 35 parts by weight of water and 10 wt% of the polyurethane emulsion were mixed, and the remaining polyurethane emulsion and 0.06 parts by weight of ammonium persulfate were added dropwise at 85° C. with stirring for 3 h. After the addition was completed, the temperature was kept for 30 min, then cooled to 60° C., 0.04 parts by weight of tert-butyl hydroperoxide and 0.03 parts by weight of isoascorbic acid were added dropwise for 15 min, and the temperature was cooled to room temperature to obtain a modified polyurethane resin.

[0068] The polyol is a mixture of polycarbonate diol, polycaprolactone diol and polypropylene glycol in a mass ratio of 1:1.6:0.2.

[0069] The weight average molecular weight of the polycarbonate diol, the polycaprolactone diol, and the polypropylene glycol was 2,000.

[0070] The polyisocyanate is toluene diisocyanate.

[0071] The weight average molecular weight of polyethylene glycol monomethyl ether is 1400.

[0072] The acrylic monomer is a mixture of butyl methacrylate, methyl methacrylate and hydroxyethyl acrylate in a mass ratio of 0.4:1:1.5.

[0073] The preparation method of the modified water-based styrene acrylic resin is as follows: by weight:

[0074] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.12 parts by mass of graphene oxide were mixed, ultrasonicated for 30 minutes, 50 parts by mass of N,N-dimethylformamide were added, stirred at 110° C. for 2 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;

[0075] (2) 10 parts by mass of modified graphene oxide and 64 parts by mass of ethanol were mixed, and then an aqueous solution of nano-titanium oxide was added, stirred at 55° C. for 3 h, centrifuged, and freeze-dried to obtain modified graphene oxide;

[0076] (3) 30 parts of methyl methacrylate, 17 parts of hydroxyethyl acrylate, 6 parts of styrene, 45 parts of organosiloxane, 3 parts of emulsifier, 0.4 parts of ammonium persulfate, 1 part of 1,4-butyrolactone, 0.38 parts of 1,4,7-trimethyl-1,4,7-triazacyclononane, 5 parts of modified graphene oxide and 220 parts of deionized water were mixed, and the mixture was heated to 80° C. for polymerization reaction for 3-4 hours under stirring, and then cooled to 40° C., and then ammonia water was added to adjust the pH of the system to 7, and stirring was stopped and the mixture was cooled to room temperature to obtain a modified water-based styrene acrylic resin.

[0077] The organic siloxane monomer is a mixture of vinyl trimethoxy silane, vinyl triethoxy silane and allyl trimethoxy silane in a mass ratio of 1:1.3:0.2.

[0078] The emulsifier is octylphenol polyoxyethylene ether, and the octylphenol polyoxyethylene ether is OP-4.

[0079] The mass ratio of modified graphene oxide and TiO2 is 10:1.

[0080] The graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and was purchased from Xianfeng Nano.

[0081] The average particle size of nano titanium oxide is 15nm, and the specific surface area is 30-100m 2 / g. Beijing Dekedaojin Technology Co., Ltd.

[0082] The dispersing aid is DI SPERBYK-192.

[0083] The leveling agent is BYK-358N leveling agent from Germany.

[0084] The defoaming agent is TEGO904W defoaming agent.

[0085] The preparation method of the bending-resistant water-based transfer coating is as follows: weigh the components, blend them, stir them evenly, and filter them through a 300-mesh filter to obtain the coating.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is: 8 parts of modified polyurethane resin; 14 parts of modified water-based styrene acrylic resin.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is: 19 parts of modified polyurethane resin; 3 parts of modified water-based styrene acrylic resin.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that the polyol is a mixture of polycarbonate diol, polycaprolactone diol and polypropylene glycol in a mass ratio of 1:1:1.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 1 is that the weight average molecular weight of the polycarbonate diol, the polycaprolactone diol and the polypropylene glycol are all 1500.

[0094] Comparative Example 5

[0095] The difference between this comparative example and Example 1 is that the acrylic monomer is a mixture of butyl methacrylate, methyl methacrylate and hydroxyethyl acrylate in a mass ratio of 1:1:1.

[0096] Comparative Example 6

[0097] The difference between this comparative example and Example 1 is that the average particle size of nano titanium oxide is 60nm, the specific surface area is 20-60m 2 / g. Beijing Dekedaojin Technology Co., Ltd.

[0098] Comparative Example 7

[0099] The difference between this comparative example and Example 1 is that the sheet diameter of graphene oxide is 10-20 μm and the thickness is 1.2-1.5 nm. It was purchased from Shanghai Xiangtian Nanomaterial Co., Ltd.

[0100] Comparative Example 8

[0101] The difference between this comparative example and Example 1 is that the organosiloxane monomer is a mixture of vinyltrimethoxysilane, vinyltriethoxysilane and allyltrimethoxysilane in a mass ratio of 1:1:1.

[0102] Performance Testing

[0103] The water-based transfer coatings prepared in Examples 1-2 and Comparative Examples 1-8 were subjected to performance tests.

[0104] Peelability: Stick 3M tape on the coating film, pull the 3M tape at a 45-degree angle, and observe whether the coating is completely peeled off. If it is completely peeled off, it is qualified, otherwise it is unqualified.

[0105] Holographic brightness: Holographic molding machine, observe the brightness of the holographic image after molding, the brightness is divided into five levels from high to low, 5-1.

[0106] Bending resistance: After aluminum is plated on the coating, it is folded inside out at 180°C for 10 times and the tape is peeled off. If less than 5% of the aluminum layer falls off at the crease, it is qualified, otherwise it is unqualified.

[0107] Temperature resistance: Use a heat sealer at a fixed pressure of 500kPa and a time of 1s to directly press the transfer card. The temperature at which deformation is visible to the naked eye is taken as the maximum temperature that the coating can withstand.

[0108] Table 1 Performance test results

[0109]

[0110] It can be seen from the above performance test results that the water-based transfer coatings of Examples 1-2 have excellent bending resistance and holographic brightness, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect between the components.

[0111] However, since the necessary technical solutions were not adopted in the comparative examples, the corresponding performance tests were obviously worse than those of the embodiments. In comparative examples 1-5, the preparation method of the modified waterborne polyurethane was changed, and it can be seen that the bending resistance effect decreased, proving that the preparation method of the modified waterborne polyurethane has an important influence on the bending resistance effect. In comparative examples 6-8, the modified waterborne styrene acrylic resin solution was not used, and it can be seen from the results that the holographic brightness of the waterborne transfer coating was affected. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0112] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A water-based transfer coating with bending resistance, characterized in that: The invention comprises the following components in mass fractions: 10-15 parts of modified polyurethane resin; 5-10 parts of modified water-based styrene-acrylic resin; 10-15 parts of ethanol; 55-60 parts of deionized water; 0.1-0.2 parts of dispersing aid; 0.07-0.12 parts of leveling agent; 0.1-0.13 parts of defoaming agent; The preparation method of modified polyurethane resin is: (1) 25-30 parts by weight of polyol, 25 parts by weight of polyisocyanate, 3.5-4.0 parts by weight of dimethylaminopropyl acrylamide, 1.6-1.9 parts by weight of 1,4-butanediol, 0.4-0.7 parts by weight of trimethylolpropane, and 0.5-0.7 parts by weight of polyethylene glycol monomethyl ether are mixed, and reacted at 80-85° C. until NCO reaches a theoretical value of 2.5-2.8wt%, to obtain a terminal isocyanate prepolymer; the temperature is lowered to 60-65° C., and then 52-57 parts by weight of acrylic acid monomer and 2-2.4 parts by weight of triethylamine are added to obtain a polyurethane prepolymer; (2) under stirring at 40-45° C., the polyurethane prepolymer containing acrylic acid monomers in step (1) is added dropwise to 110 parts by weight of water for 10-15 minutes, and 1.5-1.7 parts by weight of ethylenediamine is added to obtain a polyurethane emulsion; (3) Mix 30-35 parts by weight of water and 10-15 wt% of polyurethane emulsion, and add the remaining polyurethane emulsion and 0.06-0.09 parts by weight of ammonium persulfate dropwise at 80-85°C with stirring for 2-3 hours. After the addition is completed, keep the temperature for 30-40 minutes, cool it to 55-60°C, add 0.04-0.06 parts by weight of tert-butyl hydroperoxide and 0.02-0.03 parts by weight of isoascorbic acid dropwise for 15-30 minutes, and cool it to room temperature to obtain a modified polyurethane resin.

2. The bending-resistant water-based transfer coating according to claim 1, characterized in that: The polyol is a mixture of polycarbonate diol, polycaprolactone diol and polypropylene glycol in a mass ratio of 1: (1.3-1.6): (0.2-0.5).

3. The bending-resistant water-based transfer coating according to claim 1, characterized in that: The polyisocyanate is one or a combination of toluene diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, and cyclohexane dimethylene diisocyanate.

4. The bending-resistant water-based transfer coating according to claim 1, characterized in that: The weight average molecular weight of polyethylene glycol monomethyl ether is 1400-1700.

5. The bending-resistant water-based transfer coating according to claim 1, characterized in that: The acrylic monomer is a mixture of butyl methacrylate, methyl methacrylate and hydroxyethyl acrylate in a mass ratio of (0.4-0.7):1:(1.5-1.8).

6. The bending-resistant water-based transfer coating according to claim 1, characterized in that: The preparation method of the modified water-based styrene acrylic resin is as follows: by weight: (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.12-0.15 parts by mass of graphene oxide were mixed, ultrasonicated for 20-30 minutes, 50-55 parts by mass of N,N-dimethylformamide were added, stirred at 100-110° C. for 2-3 hours, centrifuged, and freeze-dried to obtain modified graphene oxide; (2) mixing 10 parts by weight of modified graphene oxide and 60-64 parts by weight of ethanol, then adding an aqueous solution of nano-titanium oxide, stirring at 55-60° C. for 2-3 hours, centrifuging, and freeze-drying to obtain modified graphene oxide; (3) 30-35 parts of methyl methacrylate, 12-17 parts of hydroxyethyl acrylate, 6-12 parts of styrene, 40-45 parts of organosiloxane, 3-6 parts of emulsifier, 0.2-0.4 parts of ammonium persulfate, 1-1.3 parts of 1,4-butyrolactone, 0.35-0.38 parts of 1,4,7-trimethyl-1,4,7-triazacyclononane and 5-7 parts of modified graphene oxide and 200-220 parts of deionized water are mixed, and the mixture is heated to 80-85°C for polymerization reaction for 3-4 hours under stirring, and then cooled to 30-40°C, and then ammonia water is added to adjust the pH value of the system to 7-7.5, and stirring is stopped and the mixture is cooled to room temperature to obtain a modified water-based styrene acrylic resin.

7. The bending-resistant water-based transfer coating according to claim 6, characterized in that: The organic siloxane is a mixture of vinyl trimethoxy silane, vinyl triethoxy silane and allyl trimethoxy silane in a mass ratio of 1: (1.3-1.5): (0.2-0.5).

8. The bending-resistant water-based transfer coating according to claim 6, characterized in that: The emulsifier is octylphenol polyoxyethylene ether.

9. The bending-resistant water-based transfer coating according to claim 6, characterized in that: The mass ratio of modified graphene oxide to TiO2 is 10:1-3.

10. Use of the bend-resistant water-based transfer coating according to any one of claims 1 to 9 in a transfer card.

Citation Information

Patent Citations

  • Highlight holographic waterborne transfer coating and preparation method thereof

    CN109321115A

  • Environment-friendly waterborne transfer coating

    CN104497743A

  • Waterborne polyurethane emulsion with flexural endurance and preparation method thereof

    CN106243319A